PEMANFAATAN ASAP CAIR TEMPURUNG KELAPA UNTUK MENGENDALIKAN CENDAWAN PENYEBAB PENYAKIT ANTRAKNOSA DAN LAYU FUSARIUM PADA KETIMUN - Imas Aisyah; Nuryati Juli; Gustan Pari (BRIN Publishing, 2013)
The liquid smoke obtained from the destructive distillation on coconut shell) at 0,25-6,0% consentration-range could in vitro to inhibit the colony growth of fungi, ie. Colletotrichum glocosporoides and Fusarium oxysporum species as much as consecutively 5,59-97,85% and 6,06-94,97%. At 7% liquid-smoke contentration the inhibition reached 100% (for both spescaer). The liquid smoke obtained from 400 C distillation temperature could inbibit fungi growth the most effectivelly, te. 16.26% for Colletotrichum glocosporoides and 15.06% for Fusarium oxysporum. In vivo, the liquid smoke at 0,5%, 1%, and 5% concentration was effective to repard (up to 100%) the antracnore disease as well as fusariom wilt that attacked the host cucumber plants. However, the liquid-omoka urte at She was not recomended due to inflicting necrosis on cucumber leaves.